Comparative Assessment of Transthoracic and Transesophageal Echocardiography for Assessment of Grading of Aortic Stenosis in Elective Aortic Valve Replacement Surgeries - Moinuddin, Gulam; Saiyed, Anjum; Garg, Arun; Yadav, Anuradha (Journal of Anaesthesia and Pain, 2025)
Background: Aortic stenosis severity assessment plays a central role in determining appropriate clinical management. Variability between imaging modalities may influence diagnostic accuracy and therapeutic decisions. This study aims to compare transthoracic echocardiography and transesophageal echocardiography in grading aortic stenosis among patients undergoing aortic valve replacement. Methods: This prospective observational study included 50 patients scheduled for aortic valve replacement, each undergoing both transthoracic echocardiography and intraoperative pre-cardiopulmonary bypass transesophageal echocardiography. Aortic valve area (AVA), mean pressure gradient, peak jet velocity, and dimensionless index were measured using standard echocardiographic techniques. Paired comparisons between the two modalities were performed using a paired t-test with α = 0.05 and a 95% confidence interval (CI). Result: Transthoracic echocardiography yielded a mean aortic valve area of 0.584 ± 0.08 cm², whereas transesophageal echocardiography measured 0.623 ± 0.07 cm², demonstrating a significant difference (p = 0.020). Transesophageal echocardiography reported a lower mean pressure gradient (39.08 ± 6.15 mmHg) and peak jet velocity (3.71 ± 0.42 m/s) compared with transthoracic echocardiography (49.14 ± 7.85 mmHg and 4.23 ± 0.53 m/s, respectively), with both parameters showing statistically significant differences (p < 0.001). No significant difference in the dimensionless index was observed between the two modalities (p = 0.250). Conclusion: Transesophageal echocardiography presents higher AVA measurements but lower pressure gradients and peak velocity values than transthoracic echocardiography, potentially altering aortic stenosis severity grading. Dimensionless index values remain consistent between modalities. Standardized evaluation protocols are required to guide the selection of the most appropriate imaging modality for accurate assessment of aortic stenosis.